The Influence of Financial Literacy, Financial Technology, and Financial Inclusion on The Financial Performance of SMEs in the Services and Trade Sectors in Pontianak City - Iva Nurfazrina; Edy Suryadi (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of financial literacy, financial technology, and financial inclusion on the financial performance of SMEs in the service and trade sectors in Pontianak City. The background of this research lies in the importance of financial literacy and inclusion in improving business sustainability, as well as the limited utilization of financial technology among SME actors. This research employs an associative method with a quantitative approach. The population consists of all SMEs in the service and trade sectors in Pontianak City, totaling 2,218 units. A sample of 150 respondents was selected using proportionate stratified random sampling. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, and F-test. The results of the F-test indicate that financial literacy, financial technology, and financial inclusion simultaneously have a significant effect on financial performance. The t-test results show that financial literacy and financial inclusion have a positive and significant partial effect on financial performance, while financial technology does not have a significant influence. The coefficient of determination (R²) is 0.071, indicating that the three independent variables explain only 7.1% of the variation in financial performance, while the remaining 92.9% is influenced by other variables not examined in this study. These findings highlight the importance of strengthening financial literacy and inclusion among SME actors to enhance their financial performance. Meanwhile, the use of financial technology still requires optimization through proper education and guidance.